Characterization of water masses in the Sulu Sea using temperature–salinity (T-S) diagrams, dissolved oxygen, and chlorophyll-a distribution - Firdaus, Muh; Mauludiyah (UIN Sunan Ampel Surabaya, 2026)
The Sulu Sea is a semi-enclosed tropical marginal basin influenced by complex exchanges between the South China Sea and the western North Pacific, resulting in distinctive hydrographic and biogeochemical characteristics. This study aims to characterize the water masses of the Sulu Sea using temperature–salinity (T–S) analysis and to examine the vertical distributions of dissolved oxygen (DO) and chlorophyll-a as indicators of biophysical processes. A key novelty of this study is the integration of T–S analysis with DO and chlorophyll-a observations to provide a comprehensive assessment of the relationships among water-mass structure, ventilation processes, and biological productivity in the Sulu Sea. The analysis was based on Conductivity–Temperature–Depth (CTD) observations collected at 22 stations during the SEAFDEC cruise in March–April 2015, with profiling depths reaching approximately 750 m. The T–S analysis identified two dominant upper-ocean water masses: Subtropical Lower Water (SLW), characterized by a salinity maximum of 34.5–34.9 psu within the thermocline layer (150–250 m), and North Pacific Upper Thermocline Water (NPUTW), which was primarily observed in the eastern stations and indicates the influence of Pacific inflow through the Bohol–Dipolog pathway. Dissolved oxygen exhibited strong vertical stratification, with high concentrations (>5 mg L⁻¹) in the surface layer and reduced values ( 2 mg L⁻¹) below the thermocline due to limited ventilation and organic matter remineralization. Chlorophyll-a was concentrated within the upper euphotic zone and near the thermocline, reflecting the combined influence of stratification and nutrient availability. The integrated analysis demonstrates that water-mass distribution, oxygen dynamics, and phytoplankton variability are closely linked to circulation pathways and vertical stratification. These findings provide new insight into the coupling between physical and biogeochemical processes in the Sulu Sea and contribute to improving the understanding of tropical marginal sea ecosystems.